Synthesis and Characterization of Lyophilized Chitosan-Based Hydrogels Cross-Linked with Benzaldehyde for Controlled Drug Release. (18th May 2020) - Damiri, Fouad; Bachra, Yahya; Bounacir, Chaimaa; Laaraibi, Asmae; Berrada, Mohammed
Abstract : In this study, chitosan-based hydrogels were produced by incorporating three drugs with a different solubility into a polymer matrix. The lyophilized chitosan salt was prepared using an innovative and less-expensive synthetic process by the freeze-drying technique. Firstly, the three drugs (caffeine, ascorbic acid, and 5-fluorouracil (5-FU)) were selected as model drugs to test the in vitro release behavior of the hydrogel. The drugs were solubilized in chitosan salt, lyophilized, and cross-linked with benzaldehyde involving the formation of a Schiff base with (–C=N-) linkage to produce a physical hydrogel. Subsequently, the physicochemical properties of N-benzyl chitosan and lyophilized chitosan salt were evaluated by Fourier-transform infrared (FTIR) spectra, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The intrinsic viscosity of the conventional chitosan was determined by the Mark–Houwink–Sakurada equation. Moreover, the kinetics of hydrogel swelling and drug release were studied by the UV-visible method at physiological conditions (pH = 7.4 at 37°C). The results show that lyophilized N-benzyl chitosan had a maximum swelling ratio of 720 ± 2% by immersion in phosphate-buffered saline solutions (PBS) (pH = 7.4 at 37°C). In vitro drug releases were evaluated in PBS, and the obtained results show that the maximum drug release after 24 h was 42% for caffeine, 99% for 5-FU, and 94% for ascorbic acid. Then, to optimize the cumulative release of caffeine, Tween 20 was added and 98% as a release percentage was obtained. The drug-loading results were investigated with the Korsmeyer–Peppas kinetic model and applied to determine the drug release mechanism.